The Causal Relationship between EFL Student’s Self Efficacy and EFL Student’s Writing Ability in Paragraph Writing Class at English Department of Universitas Negeri Padang - Pratiwi, Dian; Ovilia, Ririn (Journal of English Language Teaching, 2024)
This research discusses the challenges students face in writing English, which are characterized by anxiety, worry, and perceived deficiencies in linguistics, grammar, and vocabulary. This study investigates the causal relationship between student self-efficacy and writing ability in the context of English as a Foreign Language (EFL) students. Using causality design and quantitative descriptive methodology, researchers from Padang State University found a significant correlation between self-efficiency and writing ability from the ideation and convention dimensions. The study concluded that 26.3% of the variance in writing ability was caused by self-efficacy, supported by a high correlation value (0.222) and a significance level below 0.05. Acceptance of the hypotheses (H1, H2 and H3) underlines the influence of the role of self-efficacy on students' writing abilities. In essence, this research confirms that students' confidence in themselves has a significant impact on their effectiveness in writing English. Simply put, increased self-efficacy correlates with improved English writing ability among students.